2012
DOI: 10.1111/j.1474-9726.2012.00813.x
|View full text |Cite
|
Sign up to set email alerts
|

MFG‐E8 activates proliferation of vascular smooth muscle cells via integrin signaling

Abstract: Summary An accumulation of milk fat globule EGF-8 protein (MFG-E8) occurs within the context of arterial wall inflammatory remodeling during aging, hypertension, diabetes mellitus, or atherosclerosis. MFG-E8 induces VSMC invasion, but whether it effects VSMC proliferation, a salient feature of arterial inflammation, is unknown. Here, we show that in the rat arterial wall in vivo, PCNA and Ki67, markers of cell cycle activation, increase with age between 8 and 30-mo. In fresh or early passage VSMC isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
134
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(141 citation statements)
references
References 44 publications
7
134
0
Order By: Relevance
“…18 MFG-E8 also coordinates cell cycle molecules such MFG-E8 expression in oral squamous cell carcinoma M Yamazaki et al as proliferating cell nuclear antigen and cyclin-dependent kinase 4 to facilitate cell proliferation via integrin/ERK1/2 signaling in vascular smooth muscle cells. 36 Our present MFG-E8 knockdown experiment clearly indicated that MFG-E8 facilitates cell proliferation and acts as an anti-apoptotic factor in oral SCC. When MFG-E8 was suppressed in the present study, geminin þ cells, which were about to divide, decreased in number, while apoptotic cells, which were revealed by activation of caspase-3 and DNA fragmentation, increased in number.…”
Section: Discussionsupporting
confidence: 58%
“…18 MFG-E8 also coordinates cell cycle molecules such MFG-E8 expression in oral squamous cell carcinoma M Yamazaki et al as proliferating cell nuclear antigen and cyclin-dependent kinase 4 to facilitate cell proliferation via integrin/ERK1/2 signaling in vascular smooth muscle cells. 36 Our present MFG-E8 knockdown experiment clearly indicated that MFG-E8 facilitates cell proliferation and acts as an anti-apoptotic factor in oral SCC. When MFG-E8 was suppressed in the present study, geminin þ cells, which were about to divide, decreased in number, while apoptotic cells, which were revealed by activation of caspase-3 and DNA fragmentation, increased in number.…”
Section: Discussionsupporting
confidence: 58%
“…VSMC phenotypes can exhibit plasticity in response to modulation by the age‐associated alterations in the proinflammatory niche, characterized by a loss of contractility and abnormal proliferation and migration 7, 9, 27. These VSMC phenotypic shifts are driven by a coordinated repression/activation of contractile markers SM22α, α‐SMA, and myocardin 28, 29.…”
Section: Resultsmentioning
confidence: 99%
“…PDGF‐BB is not only a potent mitogen, but also a strong chemoattractant of VSMCs, creating a permissive tissue microenvironment for VSMC migration and invasion, promoting formation of a thickened intima in vivo 1, 2, 3, 8, 41, 42. Prior findings indicate that PDGF‐BB treatment induces invasion and migration of old VSMCs in vitro 8, 9. The capacity of VSMC to repopulate a damaged area in vitro, a model for the cellular process of thickening intimal or neointimal formation, is markedly increased after PDGF‐BB treatment 43, 44.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations